PENGELOLAAN MODAL KERJA DAN KINERJA KEUANGAN PADA TAHAP SIKLUS HIDUP PERUSAHAAN RITEL - Retno Julia Rahayu; Sri Mulyantini (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this study was to determine the effect of working capital management on financial performance at the stage of the retail company's life cycle in 2011-2020. With the dependent variable is profitability. The independent variables are working capital management and working capital strategy. The control variables are firm size, leverage, market to book value, sales growth, and capital assets growth rate. This research was conducted on the retail sub-sector listed on the Indonesia Stock Exchange during the years 2011-2020. The sample selection by purposive sampling was used from the entire population of retail sub-sector companies and the sample used was 13 companies for 10 years (2011-2020). Using Hierarchy Linear Model (HLM) with SPSS V22 program analysis. The results showed that there was an influence between working capital management and working capital strategy on financial performance at the stage of the company's life cycle.